UNETHICAL AND UNCENSORED CONTENT CREATION IN NIGERIA ENTERTAINMENT INDUSTRY: SPRINGING THE LAW TO ACTION - Paul Atagamen Aidonojie; Majekodunmi Toyin Afolabi; Omolola Janet Adeyemi-Balogun (JHR (Jurnal Hukum Replik), 2023)
Though it can be argued that the essence of the Nigerian entertainment industry meant to entertain the general public, however, it is apt to opine that the Nigerian entertainment industry also has the duty to educate, pass informative messages, and model the character of young adults and children within Nigeria. However, it has been observed that the majority of the content creation within the Nigerian entertainment industry is becoming very sexually dissipated, decadent, and corrupting the Nigerian’s child morals. It is in this regard, that this study embarks on a hybrid method of study concerning the legal and ethical issues of uncensored content creation in the Nigerian entertainment industry. In this regard, 304 questionnaires were sent to respondents resident in Nigeria. The study found that there are legal frameworks censoring content creation within the Nigerian entertainment industry. However, there are still high incidences of sexually dissipated content that could corrupt the good morals of the Nigerian child. It was therefore concluded and recommended that to effectively modeled the morals of the Nigerian child, there is a need for judicial activism and various stakeholders to swing the law into action in curtailing incidences of uncensored content creation within the Nigerian entertainment industry.